1‐Acetyl‐3, 5‐diaryl‐4, 5‐dihydro(1H)pyrazoles: Exhibiting Anticancer Activity through Intracellular ROS Scavenging and the Mitochondria‐Dependent Death Pathway. Issue 10 (19th August 2014) - Alex, Jimi M.; Singh, Sandeep; Kumar, Raj
<x xml:space="preserve">Abstract</x> A series of 17 analogs of 1‐acetyl‐4, 5‐dihydro(1H)pyrazoles (JP‐1 to JP‐17) bearing two aromatic rings at positions 3 and 5, either of which ought to be heterocyclic, were synthesized and evaluated for their anti‐proliferative potential against breast cancer (MCF‐7 and T‐47D) and lung cancer (H‐460 and A‐549) cell lines for the first time. JP‐1–7, ‐10, ‐11, ‐14, and ‐15 were observed to exhibit significant anti‐proliferative activity against MCF‐7 cells. Some notions about structure–activity relationships are reported. The investigated compounds were found to lower the intracellular reactive oxygen species in the H2DCFDA assay and also caused mitochondria‐dependent cell death in the MCF‐7 cell line, indicating a plausible mechanism of their anticancer effect.